Cryoglobulinemia in elderly patients with HCV-related chronic hepatitis - Foschi, Francesco Giuseppe (Baishideng Publishing Group Co., Limited, 2010)
Hepatitis C virus (HCV) infection affects about 3% of the world’s population and often leads to chronic liver disease. In some industrialized countries, HCV prevalence increases with age, but the optimal management of older patients has not been accurately defined. HCV infection can also lead to lymphoproliferative disorders, the most common being mixed cryoglobulinemia (MC), and also for this condition that frequently affects elderly patients, the optimal therapeutic strategy is still debated. We report the case of a 77-year-old Caucasian woman with HCV-related chronic hepatitis and cutaneous manifestations consisting of urticaria and pruritus related to MC resistant to antihistamines. The patient underwent a treatment with interferon and ribavirin. Such a treatment led to early biochemical and virological response associated with the resolution of cryoglobulinemia and cutaneous symptoms. After the end of treatment, HCV replication relapsed, but cryoglobulinemia and cutaneous symptoms did not recur. In the absence of definite treatment guidelines in this particular context, our experience suggests that the presence of symptoms related to HCV-infection that deeply affect patient quality of life warrants antiviral therapy even beyond the age limits that currently exclude patients from treatment.